Woodsia kungiana sp. nov. (Woodsiaceae), a new fern from Sichuan, China - Lu, Ngan Thi; Peng, Yu-Lan; Gao, Xin-Fen; Zhang, Li-Bing (Phytotaxa, 2019)
We describe a new species, Woodsia kungiana (Woodsiaceae), based on morphological characters. The new species is described and illustrated from high mountains of western Sichuan, China. The new species is distinguishable from the morphologically similar, closely related Woodsia cycloloba in indumentum and morphology of indusia.